Feminism in the Light of the Bioethical Pluri-Perspectivism - Jurić, Hrvoje, filozof (2010)
This text is based on the assumption that it is necessary to ensure, concerning the history, current situation and the perspectives of bioethics, a broader scope of dealing with bioethics in matters of both subject and methodology. Just as bioethics cannot from the subject-matter point of view be narrowed down to the concept of (bio)medical ethics (or even "clinical bioethics"), so it cannot from the methodological standpoint be considered a mere sub-discipline of philosophical ethics ("practical" or "applied" ethics). The broadening of the subject-matter of bioethics finds its motivation in the insight that the issues of techno-scientific era faced by modern man are interwoven with the issues concerning other living beings and nature as a whole. The understanding of the interwoven character of the issues at matter has both created a fertile ground for networking various approaches and shaped the unique platform for discussing ethical problems regarding life. It is the task of integrative bioethics to develop these initial premises. Integrative bioethics is defined as an open space of encounter and dialogue between different approaches in order to articulate, discuss and deal with ethical questions about life both in its entirety and in each of its segments, about life in all its forms, levels, phases and appearances. The key concept of integrative bioethics is pluri-perspectivism. It refers to the unification and mediation through dialogue of not only various scientific approaches (multi-, inter- and trans-disciplinarity) but also non-scientific contributions that include various forms of reflection, various cultural traditions, i.e. various standpoints relying on cultural, gender, religious, political and other particularities. In this pluri-perspective horizon of integrative bioethics, feminism figures as only one – though, it should be pointed out, obligatory – perspective, because no particular approach is sufficient in itself, but gets to expose its full value only in network and on equal footing with other perspectives. Paraphrasing a well-known saying by Kant, one could say that pluri-perspectivism (and integrative bioethics) remains empty without feminist approach, while feminist approach (and feminist bioethics) remains blind without incorporating pluri-perspective approach. If methodological postulations of integrative bioethics were consistently implemented in practice, there would be no need to develop the strategies of feminist "occupation" of bioethical space, which automatically implies the liberation of feminism from the fear of its under-representation in bioethical discussions. Thus, the basic thesis of the text is that the bioethics–feminism debate should consider the possibility of not only feminist contribution to bioethical issues and to the formation of a broader bioethical approach, but also bioethical (in the previously determined integrative sense) contributions to self-understanding and auto-conceptualization of feminism.
Projekt MZOS
ENG